Population and development: study of the inter-relationship between socio-economic development and demographic trends - Malgavkar, P.D.; Panandiker,V.A.Pai (Bombay, 1982)
The cry against coercion in family planning and the general. feeling that development is the best contraceptive', led us to undertake a study of the socio-economic development in the Indian states to see if it had any influence on the birth rate, Whilst undertaking the study, we were conscious of the importance of the family planning policy and implementation efforts in reducing the birth rate. Yet we have not taken any family planning indicators into consideration. Our view was that family planning programme, being centrally sponsored, theoretically, the family planning services are expected to be uniform throughout the country. If there are any variations in the family planning programme and performance, these would be accounted for by the socio-economic variables prevalent in a particular state.
Keywords: Population